Hubungan Pengetahuan Tugas Perkembangan Keluarga dengan Penerapan Stimulasi Perkembangan pada Anak Usia Pra Sekolah - Tressia, Tressia Febrianti; Nursasi, Astuti Yuni; Fitriyani, Poppy (STIKES Ngesti Waluyo, 2022)
The development of a child is a fundamental part of human development; this emphasizes the architecture of a person's brain formed at the beginning of life, which comes from genetic and environmental influences. There are two important factors that influence a child's development, namely genetic factor and environmental stimulation factor. Stimulation has an important role in the growth and development of children because the child's brain develops very quickly when it is stimulated. The main task of a family that determines the child's ability is on the task of family in every stage of family development. This study aims to determine the correlation between knowledge of family development tasks and the application of developmental stimulation in preschool-aged children. The research design used was quantitative research with a correlational descriptive method and a cross sectional study approach. The data obtained from 242 respondens and then analyzed using bivariate analysis (chi-square test). After analyzing the data, the results showed that the value of p=0.000 (<α 0.05). Hence, there is a significant correlation between knowledge of family development tasks and the application of developmental stimulation in pre-school-aged children. Families who have good knowledge of family development tasks have the ability to perform developmental stimulation 22.6 times greater than families who have less knowledge. Family knowledge about good family development tasks will have an impact on meeting children's needs. The children who get good stimulation could have a better impact on their development. The result of this study is expected to be the basis for Community Nurses who work in primary health services to be able to carry out promotive and preventive efforts with a family approach.